Synthesis and characterization of a metal-organic NLO material: Tetrakis(thiourea)cobalt chloride. (October 2019) - Jalel, Boutheina; Ennaceur, Nasreddine; Hawech, Sirine; Henchiri, Rokaya; Bouguerra, Wided; Ledoux-Rak, Isabelle
Abstract: We investigate the growth of the hybrid complex tetrakis(thiourea)cobalt chloride (TTCoC) from an aqueous solution of thiourea and cobalt chloride through a slow evaporation method that yields good-quality crystals. Different analyses confirmed that TTCoC crystal is a good nonlinear optical material. The crystal system and parameters were determined by X-ray diffraction analysis, which showed that the crystals crystallize in the tetragonal system with non-centrosymmetric space group P42/n. Within this structure, each Co 2+ ion is bordered by four sulfur atoms and two chlorine atoms, which allows it to adopt an octahedral coordination geometry. The functional groups in the complex were confirmed by Fourier transform IR spectroscopy. Furthermore, the percentages of the different elements present in this compound were identified through energy-dispersive X-ray analysis. The UV–visible spectrum confirmed that TTCoC crystal has transmittance as high as 59.6%. The optical band gap energy of TTCoC was obtained from the Tauc plot of ( αhν ) 2 versus hν . Its value is equal to 4.6 eV. Thermogravimetric analysis and differential scanning calorimetry revealed stability up to around 110 °C. The nonlinear optical properties of the crystal were studied by the Kurtz-Perry technique, and the efficiency of its second harmonic generation was found to be equal to that of potassium dihydrogen phosphate single crystal. This result was confirmed by theoretical calculations of the polarizability and the first hyperpolarizability. To determine the closest contacts within the crystal, Hirshfeld surface analysis was performed. Finally, according to the fingerprint plots, we can attribute the dominant interaction present within the structure to hydrogen bonds. Graphical abstract: Image 1 Highlights: Detailed crystallographic study of tetrakis(thiourea)cobalt chloride (TTCoC) single crystal. High second harmonic generation efficiency practically equal to that of standard potassium dihydrogen phosphate. By computational chemistry at the DFT level, the first hyperpolarizability ( β ) of TTCoC is evaluated as 1.34765 × 10 −26  esu. Hirshfeld surface analysis of TTCoC crystal. Potential for nonlinear optical applications.